Analisis Bibliometrik Pengembangan Ekonomi Pesantren di Indonesia - Litriani, Erdah; Panorama, Maya; Pertiwi, Dian (Universitas Batanghari Jambi, 2024)
The purpose of this research is to identify and analyze scientific literature with bibliometric analysis to find the main topics, authors, sources, articles that are most widely cited in Indonesia that discuss economic development in Islamic boarding schools in relation to economic independence and entrepreneurship and empowerment. Another objective is to understand the conceptual, intellectual, and social structures of the literature on various forms of pesantren economic development. This study uses journal articles indexed on Google Schoolar which are published using the publish and perish search engine version 8 in 2016 to 2023. To obtain a map of research results regarding the economic development of Islamic boarding schools, data from Publish or perish are exported into RIS file form and then analyzed using Vosviewer (VV) application. The research results show that the publication of research results from 2016 to 2022 has experienced a fluctuating increase. Through Vosviewer's visualization, the development map of Islamic boarding school economic development research is divided into 5 clusters. Cluster 1 consists of 12 items, cluster 2 has 9 items, cluster 3 has 8 items, cluster 4 has 7 items, and cluster 5 has 5 items. Opportunities for further research according to Vosviewer's analysis are the independence of the students, economic welfare, and government attention.